Transitioning from Industry 4.0 to Society 5.0: Opportunities and Challenges, a Literature Review - LEI RONGMING (International Journal of Multidisciplinary Research and Studies, 2023)
Increased operational efficiency and the creation and implementation of new business models, services, and products ushered in the age of Industry 4.0, which in turn changed manufacturing and production processes. In particular, the goal for Industry 4.0 was to increase the manufacturing systems' efficiency and sustainability. Furthermore, system digitization and digitalization were prioritized, opening up possibilities for future development. The present technological progress, however, is focused more on systems and machines than on humans. Therefore, several nations have already started coordinating efforts to create Industry 5.0, which centers on creating technology, systems, and services with people in mind. Society as a whole will be affected by the changes brought about by Industry 5.0, and a new society, Society 5.0, will be born as a result. Industry 4.0 advancements will prioritize making their new tools and technology more socially and human-centered. Consequently, the next phase of industrial development, dubbed "Industry 5.0," will place a premium on promoting environmental and human health and wellness. Human-centered, resilient, and sustainable design will be at the forefront of Industry 5.0, building on the groundwork provided by the previous iteration. Therefore, the authors of this study want to present sufficient reasons for adopting Industry 5.0 as a framework for allowing industry and rising society trends and requirements to coexist by conducting a critical literature assessment. This study is significant because it contributes a framework that may help with the evolution from Industry 4.0 to Society 5.0.